Influenza surveillance on 'foie gras' duck farms in Bulgaria, 2008–2012. Issue 2 (March 2016) - Marinova‐Petkova, Atanaska; Georgiev, Georgi; Petkov, Todor; Darnell, Daniel; Franks, John; Kayali, Ghazi; Walker, David; Seiler, Patrick; Danner, Angela; Graham, Allison; McKenzie, Pamela; Krauss, Scott; et al.
Abstract : Objectives: Ducks can shed and spread influenza A viruses (IAVs) while showing no disease signs. Our objective was to clarify the role of 'foie gras' ducks in the circulation of IAVs in Bulgaria. Methods: Monthly avian influenza surveillance was conducted on 63 'foie gras' duck farms, 52 of which were surveyed throughout the study between November 2008 and April 2012. Virologic and serologic samples were collected and tested. During this time, wild bird samples were collected at major wild bird‐resting areas near the Black Sea coast and Danube River. Results: The study showed high isolation frequency of low‐pathogenicity avian influenza viruses. In the raising population (<75 days old), subtypes H3, H4, and H6 were detected monthly and H5 LPAIV, sporadically. Different subtypes (H1, H10, H11) were isolated from the fattening premises (75‐ to 100‐day‐old ducks), suggesting different routes of introduction. Only 6 of the 52 farms that were surveyed both virologically and serologically were influenza‐free throughout the study, possibly due to higher biosecurity measures implemented. No evidence of direct transmission of IAV from wild birds was found. Wild bird surveillance showed low isolation frequency of IAV. IAV prevalence of 0·55% for migratory ducks and 0·53% for migratory geese was estimated in November–December 2011 and January–February 2012, respectively, at two ornithologically important locations near the Black Sea coast. Conclusions: The 'foie gras' duck farms in Bulgaria are an optimal niche where Eurasian‐like IAVs are maintained and reassorted unapparent to farmers and veterinarians.